(untitled) (Research, Society and Development, 2021)
The addition of fluor public water supplies and its monitoring are important measures to prevent tooth decay and control dental fluorosis. This research sought to analyze and monitor fluoride levels in water supplies, in the city of Penedo, AL, Brazil. A quantitative approach was taken, outlined as follows: 1. An epidemiological survey was taken with 2335 schoolchildren (aged 7-12 years); degree of fluorosis was classified according to Dean (0=normal to 5=severe), and determined by a trained and calibrated (kappa=0.95) team composed of dentists, community health workers, and oral health assistants. 2. Fluoride ion concentration was surveyed from 2014 to 2018 at the Water and Sewage Service (SAAE). 3. The water supply of 11 schools was monitored monthly for 6 consecutive months (from 2019 to 2020). Fluoride analysis was performed using the specific electrode method (mg F/mL). The analysis of fluoride ions between schools was performed using the Kruskal-Wallis test. The results show that 56.1% of the students had some degree of fluorosis, predominantly Grade I and II (p=0.103). The fluoride ion concentrations reported by SAAE (0.8428 – 0.9025 mgF/mL) were significantly different from those evaluated by the researcher (0.9372 – 1.0394 mgF/mL) (p=0.0103). The prevalence of dental fluorosis in schoolchildren aged 7-12 years in the city of Penedo, AL, is high, especially the very mild or mild cases. The concentration of fluoride ions in the public water supply is above that recommended for the city.